PENENTUAN KEPEMILIKAN SAHAM PEMERINTAH DALAM PERUSAHAAN PENANAMAN MODAL ASING (PMA) PADA SEKTOR PERTAMBANGAN: (STUDI MENGENAI KEPEMILIKAN SAHAM PT. SORIKMAS MINING DI KAB. MANDAILING NATAL) - IRWANDA ANASTASIA (PREMISE LAW JURNAL, 2016)
As a country with unlimited mineral and coal, Indonesia need Government’s role as ruler for these resourches in an effort to regulate their use optimalisasi revenues for it’s people prosperity. PT Sorikmas Mining (SMM) is one of company that use Work Contract there in regarding the company’s capital investment with The govermnet’s shareholding inthe field of Work  Contract VII Generation. This research is descriptive analytic research that describe, explain and analyze the determination of government shareholdings in foreign companies in the mining sector with normative juridical method, which refers to the legal norms contained in the legislation, and with regard to principles and norms in foreign investment The result of this analysis show that as a company who invest in Indonesia, PT SMM also imposed the obligation to divest its stake,in accordance with the Government Regulation No.24 Tahun 2012 abaut Mining, Mineral and Coal. The implementation of the mining activities carried out by PT Sorikmas Mining will be monitored well by the Government directly from the company if the government became part of the shareholders so that they can do governance oversight function of mining companies.   Keywords:  Foreign Investment, Divestment Share, Contract of Work